PERTUMBUHAN DAN HASIL TANAMAN JAGUNG MANIS (Zea mays L. Saccarata Sturt) VARIETAS EXOTIC PADA BERBAGAI METODE OLAH TANAH KONSERVASI - Gusti Ketut Harthane; Dulbari Dulbari; Yuriansyah Yuriansyah; Denny Sudrajat (JURNAL AGROTROPIKA, 2026)
This study aimed to evaluate the effects of various conservation tillage methods on the growth and yield of sweet corn (Zea mays saccharata Sturt) of the Exotic variety. The research was conducted at the experimental field of the State Polytechnic of Lampung from September to December 2023, using a Randomized Complete Block Design (RCBD) with nine treatment combinations of chemical fertilizer, organic fertilizer, mulch, and tillage, each replicated three times. The observed parameters included plant height, number of leaves, leaf greenness, cob length and diameter, and cob weight. Statistical analysis showed that all treatments had no significant effect on the observed parameters (p > 0.05). However, descriptively, mulch-based treatments and combinations with chemical fertilizers showed positive trends in growth and yield. Treatment P7 (mulch) resulted in the highest plant height and cob weight, while P1 (chemical fertilizer + tillage) tended to produce the largest cob diameter and highest number of leaves. The use of mulch from edamame residue was proven to help retain soil moisture and improve nutrient uptake efficiency. These findings indicate that conservation tillage systems utilizing mulch and crop rotation can be a sustainable cultivation strategy to enhance sweet corn productivity.